Translation and validation of the meat attachment questionnaire (MAQ) in a French general practice population - Bruno Delaunay; Benoit Tudrej; Augustin Bernard; Alexandra Dupuy; Claire Malavergne; Trystan Bacon; Paul Sebo; Hubert Maisonneuve (Scientific Reports)
Abstract Meat consumption has significant implications for both individual health and the environment. Understanding individuals’ attachment to meat is crucial for designing effective interventions to reduce consumption. The MAQ is a tool developed to assess individuals’ attachment to meat. This study aims to translate and validate the MAQ into French for use in a general practice population in France. The study was conducted in three phases: translation, pretesting through cognitive interviews, and testing through a cross-sectional study of general practice patients. Descriptive, factorial, and internal consistency analyses were performed to validate the French version of the MAQ. The French version of the MAQ consists of 17 items in four dimensions: Hedonism, Affinity, Entitlement, and Dependence. Face validity was confirmed by cognitive interviews. The RMSEA and CFI were 0.06 and 0.92 respectively, showing acceptable goodness-of-fit. Internal consistency was demonstrated with Cronbach’s alpha and Loevinger’s H coefficients exceeding 0.7 and 0.3, respectively. The French version of the MAQ is a valid and reliable tool for assessing individuals’ attachment to meat in a general practice population. Its application shows promise for the design of targeted interventions to reduce meat consumption, benefiting both individual health and environmental sustainability.